An in Vitro Biocompatibility Study of Conventional and Resin-modified Glass Ionomer Cements - Rodríguez, IA; Rozas, CA.; Campos-Sánchez, F.; Alaminos Mignorance, M.; Uribe Echevarria, J.; Campos A. (2019)
Purpose: To evaluate the biocompatibility of a glass-ionomer (GIC) and a resin-modified glass-ionomer cement (RM-GIC), cell viability was examined in a model of human gingival fibroblasts using morphological, biochemical, and ionic patterns by means of phase contrast microscopy, lactate dehydrogenase (LDH) release, and quantitative x-ray microanalysis (EPXMA). Materials and Methods: The GIC Ketac-Molar Easymix (3M ESPE) and the RM-GIC Vitrebond (3M ESPE) were compared in human gingival fibroblasts exposed to the cements for 72 h. As controls, fibroblasts cultured with DMEM culture medium (negative control) and with 1% triton × (positive control) were used. Results: Light microscopic findings showed greater morphological alterations in cells exposed to RM-GIC than to GIC. The relative percentage of LDH released from the cells to the supernatant was significantly higher in RMGIC cultures than in the control. Quantitative x-ray microanalysis showed that cultures exposed to RM-GIC were characterized by an increase in intracellular Na and a decrease in intracellular Cl and K. These changes in ion composition were significant compared to control and GIC cultures. Conclusion: The three indicators of cellular biocompatibility after 72 h of exposure showed that RM-GIC led to more marked alterations than GIC in human gingival fibroblasts.